Study of Antioxidant Activity of the Derivatives of Quinoline-4-carboxylic Acids by the Modification of Isatin via Pfitzinger Reaction - Fikriya, Sakti Hidayati; Cahyana, Antonius Herry (Makara Journal of Science, 2023)
In this study, a quinoline-4-carboxylic acid derivative was synthesized through Pfitzinger reaction. In this reaction, isatin is modified via its reaction with ketone and refluxed for 24 h to obtain quinoline-4-carboxylic acid. The presence of a carboxylic group was identified by Fourier Transform Infrared (FTIR) spectroscopy and ultraviolet–visible (UV-Vis) spectrophotometry. The results showed that the absorption peaks of C=O and O–H stretching’s were detected in the range of 1724–1708 and 3436–3242 cm−1, respectively. In the UV-vis spectrum, a shift in the absorption peak was observed toward a larger wavelength, which is referred as a bathochromic shift. The formation of quinoline-4-carboxylic acid derivative was also characterized using the mass spectrometry method. The modification of isatin aims to increase antioxidant activity to obtain quinoline-4-carboxylic acid, which has a better inhibition percentage than isatin. Antioxidant tests were conducted using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. The antioxidant activity is measured based on the ability of quinoline-4-carboxylic acid derivative to donate hydrogen radicals, which revealed that the product had a relatively better inhibitory effect than isatin. At a concentration of 5 mg/L, isatin did not show antioxidant activity with the DPPH method. By contrast, the inhibition percentages of 2-methylquinoline-4-carboxylic acid and 2-(4-methylphenyl)quinoline-4-carboxylic acid were approximately 30.25% and 40.43%, respectively. Furthermore, the presence of an aromatic ring makes the antioxidant activity.